Democracia e eleição de dirigentes escolares no sistema municipal de ensino de Belém: análises e perspectivas - GUEDES, Maria Gorete Rodrigues Cardoso (Universidade Federal do Pará, 2011)
The research was turned toward the inquiry of the institutionalization process of the direct election of pertaining to school controllers in the Municipal System of Education of Belém, as dimension of the projects pedagogical politicians and produced by the municipal managements in the period of 1993 the 2006. The objective was to analyze the advances, limits and perspectives of the proposals of election of controllers, established under the optics of the plan of the deed of division-legal orientations of the educational system. The used methodological orientation was of the bibliographical research and the documentary analysis. Through a detailed study of main official documents produced by the municipal administrations, it was intended to identify to the scienters politics of the respective governments in the delimited period and to characterize its respective educational projects and proposals of election of pertaining to school controllers, as well as perceiving the conception of democracy and inherent democratic management to the same ones. The results reached with the inquiry in take them to infer that the process of democratization of the pertaining to school management in the SME, saw the election of pertaining to school controllers, is not something finished and defined, but a permanent construction, marked for gone and comings, jibs and advances, that point with respect to distinct perspectives and horizons and reach the most different ideological shades. Therefore, it can be affirmed that the pertaining to school democracy in the SME is not, but is being constructed in accordance with to the possibilities and constaints presented at each historical moment and with the capacity of the educational actors to incorporate the established institucional democracy.